Interferon-? Expression in Histopathological specimens with Invasive Breast Carcinoma of No Special Type at Menopause and Reproductive age - Yuni Prastyo Kurniati; Syafira Anggraini Khusna; Elisna Dwi Anggraeni (Konsorsium LPPM Perguruan Tinggi Muhammadiyah 'Aisyiyah (PTMA) Koordinator Wilayah Jawa Tengah - DIY, 2022)
Invasive breast carcinoma of No special type is the most common type of breast cancer with a prevalence of 50% to 80%. Breast cancer is an important threat in women of menopausal age, and only 5-7% are diagnosed under the age of 40 years. The most common risk factor for cancer is immune system disorders. There is a decrease sex hormone during menopause that results disruption of the body's immune system in the elderly. Women of reproductive age have elevated levels of T CD4+ and immunoglobulins in the circulation. Naïve CD4+ cells produce more IFN-?. IFN-? is a cytokine at innate and adaptive immunity that has proven important in antitumor immune response. Purpose: This study proves IFN-? expression in NST histopathology based on reproductive and menopause age. Method: Research is observational analytic with a cross sectional approach. NST parafin blocks specimens as many as 16 samples from the menopause age and 15 samples from the reproductive age. Then, the painting and examination of Immunohistochemistry IFN-?. Results: Fisher tests get a value of p = 0.5 at the age of menopause and the Mann Whitney test with a value of p = 0.823 at reproductive age. Conclusion: There is no association between menopausal age and reproductive age with IFN-? expression in the histopathology specimen of Invasive breast carcinoma of No special type patients. However, there was an increase in IFN-? expression in the specimen of reproductive age by 60%.